Experimental study of transient thermal creep and other phenomena of concrete at high temperature - Colina, Horacio; Moreau, Gilles; Cintra, Daniel (Journal of Civil Engineering and Management, 2004)
This paper deals with experimental study of transient thermal creep and other parameters, as elastic and free thermal strain, of ordinary, high‐strength and high‐performance concrete at high temperature. An original test device can reproduce accident and service conditions with a homogeneous distribution of temperature inside the specimens. Constant values of heating rate and force (when the specimen is loaded) are applied. Successive constant temperature levels are reached and maintained during the necessary time to ensure internal stabilisation. To observe the importance of changes in concrete properties after a first heating cycle, some specimens are submitted to a second one. In order to show the performance of the experimental methods, some results are presented and discussed. First Published Online: 14 Oct 2010